Complexidade e simplicidade: paradoxo na estrutura composicional do Prelúdio da Suíte Nº. 5 para Violoncelo Solo de J.S. Bach - Campos, Luz Yanaina álvarez (2011)
This research aims to demonstrate the stylistic origin of Bach´s Prelude from the Cello Suite No. 5, offering new elements and sources for interpretation of the work. Thus, we have taken the book Dance and the Music of J.S. Bach, written by Little and Jenne, as theoretical reference in order to establish the importance of the French court dances for the compositional style of J.S. Bach. From this study, we have pointed the main characteristics of the passepied, as well as its compositional structure, for we have found a close relationship between this French court dance and the second section of the Prelude. Thus, the main focus of the research was to define and demonstrate that, although written in the complex structure of a fugue, the second section of the Prelude from 5th Suite is clearly based on a passepied. Thereby establishing new interpretative parameters related to style, tempo and character. Aspects that are certainly relevant to the interpretive approach to the work. At the same time, we have prepared a new edition of the Prelude, for comparative purpose, based on J.S. Bach´s lute transcription and the cello manuscript copy made by Anna Magdalena Bach. Through this comparative analysis, it was possible to emphasize the similarities and discrepancies between the two versions. As a result, we have found new structural elements related to the idiomatic language, which reflects to the general understanding of the work. This study assumes that Bach paradoxically combines the complex structure of the fugue with the simple elements characteristic of the passepied dance. Aspects that reinforce and expand the understanding of the piece, in order to build a new interpretation of the Prelude, based on the stylistic origin under which the fugue was elaborated.